2020
DOI: 10.5694/mja2.50529
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk assessment for Aboriginal and Torres Strait Islander adults aged under 35 years: a consensus statement

Abstract: Summary Cardiovascular disease (CVD) is a leading cause of preventable morbidity and mortality in Aboriginal and Torres Strait Islander peoples. This statement from the Australian Chronic Disease Prevention Alliance, the Royal Australian College of General Practitioners, the National Aboriginal Community Controlled Health Organisation and the Editorial Committee for Remote Primary Health Care Manuals communicates the latest consensus advice of guideline developers, aligning recommendations on the age to commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…Incidence rates for participants in the 4th waist circumference quartile were 38.3% for males and 47.2% for females [43]. The development of CVD at younger ages has led to recent calls for risk assessment for Aboriginal and Torres Strait Islander adults aged 35 years and under that are supported by the findings from this study [44].…”
Section: Discussionsupporting
confidence: 72%
“…Incidence rates for participants in the 4th waist circumference quartile were 38.3% for males and 47.2% for females [43]. The development of CVD at younger ages has led to recent calls for risk assessment for Aboriginal and Torres Strait Islander adults aged 35 years and under that are supported by the findings from this study [44].…”
Section: Discussionsupporting
confidence: 72%
“…Practice advice: Before consideration of CAC scoring, assess CVD risk on clinical grounds. If the person is aged over 45 years (or over 30 years if Aboriginal or Torres Strait Islander 48 ), this should include an NVDPA absolute risk assessment 3 The 2012 NVDPA absolute risk algorithm may underestimate risk in certain populations, such as Aboriginal and Torres Strait Islander peoples, 49 or in others with known risk‐enhancing factors not fully captured in the NVDPA algorithm (Box 4).…”
Section: Recommendationsmentioning
confidence: 99%
“…Recently updated guidelines suggest screening Aboriginal and Torres Strait Islander peoples for CVD risk factors from the age of 18 years and to perform absolute CVD risk assessment from the age of 30 years 12 . It is suggested that diabetes screening should also begin from the age of 18 years unless individuals are affected by overweight or obesity, as this can increase the risk of chronic disease 13 .…”
mentioning
confidence: 99%